Recycling Space Beverage Packaging into LDPE-Based Composite Materials - Federica De Rosa; Flavia Palmeri; Susanna Laurenzi (Aerospace)
Long-term space missions require careful resource management and recycling strategies to overcome the limitations of resupply missions. In this study, we investigated the potential to recycle space beverage packaging, which is typically made of low-density polyethylene (LDPE) and PET-aluminum-LDPE (PAL) trilaminate, by developing a LDPE-based composite material with PAL inclusions. Due to the limited availability of space beverage packaging, we replaced it with LDPE powder and commercial coffee packaging for the experiments. Fourier transform infrared spectroscopy (FTIR) was employed to thoroughly analyze the composition of the commercial coffee packaging. The simulant packaging was reduced to a filler, and its thermal properties were characterized by differential scanning calorimetry (DSC), while the particle size was analyzed via scanning electron microscopy (SEM) and the bootstrap resampling technique. Composite specimens were then fabricated by incorporating the filler into the LDPE matrix at loadings of 5 wt% and 10 wt%, and their mechanical and thermal properties were assessed through dynamic mechanical analysis (DMA) and thermal conductivity measurements. The 10 wt% corresponds approximately to the radio between PAL and PE in space beverage packaging and is, therefore, the maximum usable percentage when considering a single package. The results indicate that, as the filler loading increased, the mechanical performance of the composite material decreased, while the thermal conductivity was significantly improved. Finally, 10 wt% LDPE/PAL filaments, with a diameter of 1.7 mm and suitable for the fused filament technique, were produced.